Food loss and waste data gaps in fruit and vegetable value chains: a review of the literature - Ambuko, Jane Lukhachi; Masakhwe, Sharon Mayienga; Amwoka, Emmanuel; Mujuka, Esther; Fabi, Carola (Frontiers in Horticulture, 2025)
Low consumption of fruits and vegetables (FV) is in part attributed to unavailability and cost, especially among the low-income populations. High postharvest losses contribute to low availability and cost. According to the FAO report of 2011, 44% of all the FV produced are lost or wasted along the supply chain. Although there have been efforts to reduce food loss and waste (FLW) in FV, the interventions are often misguided due to lack of reliable data on critical loss points, the causes/driver of losses, extent of losses and context-appropriate interventions. This mini review sought to highlight the FLW data gaps with a focus on FV value chains. The review used the FLW database created by FAO as an online collection of literature on FLW from 1965 to 2022. Through a stepwise review of open access articles in the FAO database and other open access sources on the internet, the extent and trends of losses (median), the number of published articles, data collection methodology and the priority value chain on FLW research in different countries within the sub-Saharan Africa (SSA) region was explored. The mini review shows that there are about 632 openly accessible publications on FLW, including 259 on cereals and pulses,190 on fruits and vegetables, 118 on Roots, tubers and oil-bearing crops and 32 on meat and animal products. Out of the 190 articles on FV globally, 66 articles focused on SSA on mango, banana and tomato. Most of the studies have focused on Asia and Africa with very few studies on FLW status in North America and Europe. Within SSA, Ghana and Kenya alone contributed 47% of the published articles on FV. Most of the studies focused on the farm level and the distribution stages accounting for 44% and 25% respectively of the published articles. This review highlights FLW data gaps and skewedness in the available data. Policies and interventions to reduce FLW towards the set targets such as sustainable development goal, SDG 12.3 require the FLW data gaps to be addressed. Otherwise, blind interventions that are not guided by reliable evidence will continue missing the target.